Unraveling the Kinematics of Sperm Motion by Reconstructing the Flagellar Wave Motion in 3D. Issue 3 (9th February 2022) - Powar, Sushant; Parast, Farin Yazdan; Nandagiri, Ashwin; Gaikwad, Avinash S.; Potter, David L.; O'Bryan, Moira K.; Prabhakar, Ranganathan; Soria, Julio; Nosrati, Reza
Abstract: Sperm swim through the female reproductive tract by propagating a 3D flagellar wave that is self‐regulatory in nature and driven by dynein motors. Traditional microscopy methods fail to capture the full dynamics of sperm flagellar activity as they only image and analyze sperm motility in 2D. Here, an automated platform to analyze sperm swimming behavior in 3D by using thin‐lens approximation and high‐speed dark field microscopy to reconstruct the flagellar waveform in 3D is presented. It is found that head‐tethered mouse sperm exhibit a rolling beating behavior in 3D with the beating frequency of 6.2 Hz using spectral analysis. The flagellar waveform bends in 3D, particularly in the distal regions, but is only weakly nonplanar and ambidextrous in nature, with the local helicity along the flagellum fluctuating between clockwise and counterclockwise handedness. These findings suggest a nonpersistent flagellar helicity. This method provides new opportunities for the accurate measurement of the full motion of eukaryotic flagella and cilia which is essential for a biophysical understanding of their activation by dynein motors. Abstract : Sperm swim through the complex environment of the reproductive tract by propagating a 3D flagellar wave. However, traditional microscopy techniques only image and analyze the motion in 2D. An automated platform is demonstrated to resolve the flagellar dynamics in 3D by reconstructing the waveform in 3D using thin‐lens approximation, indicating the weakly nonplanar and ambidextrous nature of the flagellar wave.